Nitrogen Fertilization and Glyphosate as a Growth Regulator: Effects on the Nutritional Efficiency and Nutrient Balance in Emerald Grass - Dinalli, Raíssa Pereira [UNESP]; Buzetti, Salatiér [UNESP]; Gazola, Rodolfo de Niro [UNESP]; de Castilho, Regina Maria Monteiro [UNESP]; Jalal, Arshad [UNESP]; Galindo, Fernando Shintate [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2022)
Nitrogen (N) is one of the promising nutrients for lawn growth and is required for the lawn’s proper growth and development, but it also increases mowing frequency. Glyphosate herbicide application in sub-doses, as a growth regulator, can reduce the maintenance costs without any adverse reduction in the density and nutritional status of grasses. The objective of this study was to evaluate the influences of nitrogen and glyphosate doses on the growth, aesthetic quality and nutritional status of emerald grass (Zoysia japonica Steud.). The experiment was conducted at the Research and Extension Education Farm of São Paulo State University (UNESP), Ilha Solteira, SP, Brazil, in an Ultisol. The experiment was designed as a randomized block with 12 treatments arranged in a 3 × 4 factorial scheme with 4 replications, comprised of a control (without N), 15 and 30 g N m−2 of urea, applied in five splits annually, and glyphosate doses (0, 200, 400 and 600 g ha−1 of the active ingredient, a.i.). The split N fertilization at the rate of 15 g m−2 and glyphosate at the dose of 400 g ha−1 maintained nutritional status of emerald grass. Nitrogen at the rate 15 g N m−2 (in five splits per year) was observed to produce lower growth traits, an adequate aesthetic quality and longer stability of the nutrients in emerald grasses through lower exportation, with removal of “clipping” after mowing. In addition, glyphosate, at the dose of 400 g a.i. ha−1, was efficient in reducing the leaf area, plant height, shoot dry matter and total dry matter by 18.3, 14.7, 6.8 and 8.1%, respectively, as compared to the control. However, this dose did not impair the coloration and resulted in a lower exportation of nutrients by reducing the need to replenish by fertilization. Therefore, fertilization with 15 g N m−2, associated with application of 400 g a.i. ha−1 of glyphosate, is recommended for emerald grass in the tropical savannah of Brazil.
Keywords: herbicide; lawn; nitrogen; plant nutrition; Zoysia japonicaSteud